Life History Evolution A Biological Meta-Theory for the Social Sciences - Hertler, Steven C. (Springer International Publishing, 2018)
The social sciences share a mission to shed light on human nature and society. However, there is no widely accepted meta-theory; no foundation from which variables can be linked, causally sequenced, or ultimately explained. This book advances "life history evolution" as the missing meta-theory for the social sciences. Originally a biological theory for the variation between species, research on life history evolution now encompasses psychological and sociological variation within the human species that has long been the stock and trade of social scientific study. The eighteen chapters of this book review six disciplines, eighteen authors, and eighty-two volumes published between 1734 and 2015-re-reading the texts in the light of life history evolution. .